STRATEGI ADVOKASI MELALUI PROSES NONLITIGASI DALAM RANGKA PEMBAHARUAN PROSES PERADILAN DI INDONESIA: STRATEGI ADVOKASI MELALUI PROSES NONLITIGASI DALAM RANGKA PEMBAHARUAN PROSES PERADILAN DI INDONESIA - Wahyu subakti; Syed Agung Afandi; Reski Lestari (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2023)
This study aims to explain the advocacy strategy through the non-litigation process in the context of reforming the judicial process in Indonesia. Mediation in court is an institution and empowerment of peace (court connected mediation) with a philosophical foundation that is Pancasila which is the basis of the Indonesian state, especially the fourth precept "Popularity led by Wisdom of Wisdom in deliberation/representation". In resolving disputes, there are several dispute resolution mechanisms, namely litigation, non-litigation, and advocacy. The method used in this research is literature study, with the type of qualitative descriptive research. The results explain that alternative efforts and strategies for resolving disputes with the Non-Litigation route can achieve a peace in accordance with the wishes of both parties through Mediation, Advocacy and negotiation. In its application there are two types of obstacles in non-litigation efforts to resolve land grabbing disputes, because mediation is not clearly regulated in Law no. 30 of 1999 concerning Artibrasion and Alternative Dispute Resolution. And the non-litigation efforts are legally less certain because their legality is also not explicitly regulated in Law no. 30 of 1999.